The Paradox of Mexican Migration to the US 2007-2012 - SALAS, Emmanuel Gerardo; LORÍA-DÍAZ DE GUZMÁN, Eduardo Gilberto; DÍAZ, Eliseo (Papeles de Población; Vol. 22 Núm. 87 (2016), 2016)
Based on an extension of Todaro’s (1976) canonical migration model, a Vector Error Correction Model (VECM) (2007Q3-2012Q3) was estimated. It is proved that the decline in Mexican migratory flow to the United States since 2005 has to do with the strengthening of its punitive actions aimed at undocumented immigration, and also with the rise in sectorial and regional unemployment in the US relative to Mexico’s unemployment rates. Some other additional and new factors, such as rising monetary costs, risks and dangers, including the death of migrants that trek through isolated areas, have also reduced attempts to cross into the United States.